Regulating Islamic Financial Institutions: The Nature of the Regulated - El-Hawary, Dahlia; Grais, Wafik; Iqbal, Zamir (World Bank, Washington, D.C., 2013)
More than 200 Islamic financial institutions (IFIs) operate in 48 countries. Their combined assets exceed $200 billion, with an annual growth rate between 12 percent and 15 percent. The regulatory regime governing IFIs varies significantly across countries. A number of international organizations have been established with the mandate to set standards that would strengthen and harmonize prudential regulations as they apply to IFIs. The authors contribute to the discussion on the nature of prudential standards to be developed. They clarify the risks that IFIs are exposed to and the type of regulations that are needed to systematically manage them. They consider that the industry is still in a development process whose eventual outcome is the convergence of the practice of Islamic financial intermediation with its conceptual foundations. The authors contrast the risks and regulations needed in the case of Islamic financial intermediation operating according to core principles and current practice. They outline implications for approaches to capital adequacy, licensing requirements, and reliance on market discipline. They then propose an organization of the industry that would allow it to develop in compliance with its principles and prudent risk management, and facilitate its regulation.